Perlindungan Hukum Nasabah terhadap Kecurangan (Fraud) Perbankan Berdasarkan POJK Nomor 12 Tahun 2024 - Muliana Putri; Mangaraja Manurung (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Bank fraud has become a more sophisticated threat with the rapid development of digital financial services. Phishing activities, data theft, social engineering, and misuse of customer data can lead to financial losses and erode trust in the banking sector. The purpose of this study is to analyze the effectiveness of the financial services sector in the banking sector and to evaluate the effectiveness of the anti-fraud strategy laid down in the Financial Services Authority Regulation No. 12 of 2024. This research uses normative legal methods with legal, conceptual and comparative approaches. The results show that consumers are supported by protection and fraud prevention measures, such as data protection, information transparency, customer education, grievance mechanisms for dispute resolution and sanctions against violators. Furthermore, the anti-fraud strategies laid down in the Financial Services Authority Regulations No. 12 of 2024 12, are based on four pillars: prevention, detection, investigation and reporting, and monitoring and evaluation. These initiatives strengthen governance and customer engagement, although there are still challenges in terms of technology readiness, human resources and people.